The Residual Landscape in the Petrofiction of the Harper Decade: A Reading of Don Gillmor’s Long Change - Omhovère, Claire (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2025)
A rising awareness of the irreversibility of global warming and the foretold end of fossil fuels have combined in English-Canadian literature to prompt new arrangements in the intensely visual regime of landscape. I propose to discuss these adjustments looking at Don Gillmor’s Long Change (2015), a petrofiction emblematic of the environmental concerns arising with Harper’s premiership. The novel questions the gratification of landscape by turning the gaze inward to weigh in the effects of fossil-fuel extraction on individual bodies and destinies.